Mengoptimalkan Kegiatan Intra dan Ekstrakurikuler Keagamaan Sekolah dalam Menunjang Pencapaian Kompetensi Pembelajaran Akidah Akhlak - Bagas Diva Anggara; Iwantoro; Ichwanudin (Journal Islamic Education, 2024)
Achieving quality learning competency in Aqidah Akhlak is one of the main goals of Islamic education in schools. Intra- and extra-curricular religious activities play a strategic role in supporting this learning process. This study aims to identify, analyze, and optimize the role of intra- and extra-curricular religious activities in supporting the achievement of quality Aqidah Akhlak competency. The method used is a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and document studies in Islamic-based junior high schools. The results show that intra-curricular activities such as classroom learning, thematic religious discussions, and project-based evaluations support strengthening students' understanding of the concept of Aqidah Akhlak. Meanwhile, extra-curricular activities, such as short-term Islamic boarding schools, religious competitions, and study groups, have a positive impact on character formation and the implementation of moral values in daily life. The synergy between these two activities has been proven to increase student learning motivation, create a conducive religious environment, and strengthen the relationship between theory and practice. However, optimizing these activities requires structured management, the involvement of competent educators, and support from parents and the community. The findings of this study suggest the development of an integrated guide for implementing religious intra- and extracurricular activities that align with student needs and curriculum targets. The implementation of this strategy is expected to become an effective and sustainable model for strengthening religious-based character education.